Communication on Employee Performance at Information Technology - Fajar Eryanto (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
In carrying work, employees can not be separated from communication with fellow all parties of the organization both co-workers, superiors and with subordinates. Communication is one of the right means of improving employee performance. This research focused on Communication and employee performance Information Technology LIPI Bandung. The observation unit for this research is a lecturer from permanent employee Information Technology LIPI Bandung with the total sample is 60 people. Multiple linear regression is used to analyze the effect between variables by using application SPSS 22. The result of this study shows that: generally, Communication already performs well. Communication has positive significant to employee performance information technology LIPI